2019
DOI: 10.3390/app9224813
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Deep Learning Approach for Machinery Prognostics Based on Time Windows

Abstract: Remaining useful life (RUL) prediction is a challenging research task in prognostics and receives extensive attention from academia to industry. This paper proposes a novel deep convolutional neural network (CNN) for RUL prediction. Unlike health indicator-based methods which require the long-term tracking of sensor data from the initial stage, the proposed network aims to utilize data from consecutive time samples at any time interval for RUL prediction. Additionally, a new kernel module for prognostics is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This indicates that a very deep model is not required for RUL estimation, so the benefits that the residual-and inceptionbased architectures offer are not realized. The applicability of CNNs on the N-CMAPSS data set, demonstrated in this work, and their past success on the original CMAPSS data set (Sateesh Babu, Zhao, & Li, 2016;Li et al, 2018;H. Yang et al, 2019), show the broad applicability that they have in RUL estimation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This indicates that a very deep model is not required for RUL estimation, so the benefits that the residual-and inceptionbased architectures offer are not realized. The applicability of CNNs on the N-CMAPSS data set, demonstrated in this work, and their past success on the original CMAPSS data set (Sateesh Babu, Zhao, & Li, 2016;Li et al, 2018;H. Yang et al, 2019), show the broad applicability that they have in RUL estimation.…”
Section: Discussionmentioning
confidence: 60%
“…This data set contains a large amount of run-to-failure data, so this work takes a data-based approach. Past research on the original CMAPSS data set demonstrated the applicability of convolutional neural networks (CNNs) (Li, Ding, & Sun, 2018;H. Yang, Zhao, Jiang, Sun, & Mei, 2019), long short-term memory (LSTM) (da Costa, Akeay, Zhang, & Kaymak, 2019;Zheng, Ristovski, Farahat, & Gupta, 2017;Wu et al, 2020), and hybrid methods, which merge CNN and LSTM (Zhao, Huang, Li, & Iqbal, 2020) for RUL estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Deep CNN architectures have been proven to provide excellent performance on time series for predictive maintenance in recent works [6,35,[38][39][40]. Concretely, a solution based on 2D convolutions with 1D filters and no pooling layers was proposed in [6] for the prognostics benchmark problem [11].…”
Section: Deep Learning Prognostics Modelmentioning
confidence: 99%
“…Since its release as PHM Challenge [10] in 2008, the CMAPSS dataset [11] has been one of the most widely used prognostics datasets. Some recent examples that are also among the best performing prognostics models applied to the CMAPSS dataset are deep learning based methods such as convolutional neural network (CNN) [12,13], long shortterm memory networks (LSTM) [14][15][16][17][18][19] or hybrid networks combining CNN and LSTM layers [20,21]. The CMAPSS dataset provides simulated run-to-failure trajectories of a fleet comprising large turbofan engines.…”
Section: Introductionmentioning
confidence: 99%